2010
DOI: 10.1007/s00170-010-2804-2
|View full text |Cite
|
Sign up to set email alerts
|

The performance of PCD tools in high-speed milling of Ti6Al4V

Abstract: Tool performance of conventional tools is poor and a major constraint when used in milling titanium alloys at elevated cutting speeds. At these high cutting speeds, the chemical and mechanical properties of Ti6Al4V cause complex wear mechanisms. In this paper, a fine-grain polycrystalline diamond (PCD) end mill tool was tested, and its wear behavior was studied. The performance of the PCD tool has been investigated in terms of tool life, cutting forces, and surface roughness. The PCD tool yielded longer tool l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(26 citation statements)
references
References 18 publications
2
24
0
Order By: Relevance
“…Ti6Al4V combines an exceptionally low thermal conductivity, high chemical reactivity at the temperatures encountered in contemporary high productivity machining, and a low modulus of elasticity [1]. So the cutting speeds (v c ) are limited to relatively low values [2]. When Ti6Al4V is milled, high temperatures at the cutting tool/work piece interface and prominent friction phenomena are encountered.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ti6Al4V combines an exceptionally low thermal conductivity, high chemical reactivity at the temperatures encountered in contemporary high productivity machining, and a low modulus of elasticity [1]. So the cutting speeds (v c ) are limited to relatively low values [2]. When Ti6Al4V is milled, high temperatures at the cutting tool/work piece interface and prominent friction phenomena are encountered.…”
Section: Introductionmentioning
confidence: 99%
“…Ultimately it presents a very real risk factor in aerospace manufacture [4]. In civil aviation, scheduled inspections to detect early fatigue crack are extensive.…”
Section: Introductionmentioning
confidence: 99%
“…This may be due to the formation of the serrated chip and vibration (chattering). The cutting force and temperature from turning of titanium workpiece with PCD tool are validated with the research findings of Oosthuizen et al [22] and Pan [23] respectively. From the validation test, the cutting force and temperature show the maximum variation of 22.34% and 34.86% respectively.…”
Section: Fig 1 Interaction Plot For A) Resultant Force Under Turninmentioning
confidence: 60%
“…Recent publications when milling titanium with PCD tooling have also shown favourable results at higher speeds than used for WC. When cutting Ti-6Al-4V, Oosthuizen et al [15] reported on tool life/wear when operating at 100-300 m/min, with slower wear progression and reduced cutting force occurring at 200 m/min. Similarly, Li et al [16] identified 250 m/min cutting speed as providing the lowest flank wear in face milling tests operating at up to 1000 m/min with a feed and axial depth of cut of 0.05 mm/tooth and 0.5 mm respectively.…”
Section: Introductionmentioning
confidence: 97%